Annotated list of the Tortricidae (Lepidoptera) of Honduras - Passoa, Steven C.; Brown, John W.; Dombroskie, Jason J.; Young, James D.; Berghe, Eric Van Den (Zootaxa, 2025)
We present an annotated list of 109 Tortricidae from Honduras. Seventy of them represent described species whereas the remaining 39 were unidentified or undescribed specimens identified only to genus. All but 12 of these taxa are reported from Honduras for the first time. The list is based on personal collecting experiences, examination of institutional research collections, a review of relevant literature, and images posted on iNaturalist. Where known, we provide summaries of host plants and relevant geographic distributions.